Mentor.Zen-Net: a revolutionary mentoring app for fostering innovative entrepreneurship / Siti Hajar Mohd Hussain ... [et al.] - Mohd Hussain, Siti Hajar; Md Mansor, Mohamad Naqiuddin; Mohamad, Masilah; Tasnim, Rahayu (Universiti Teknologi MARA, Kedah, 2024)
This business plan outlines the development of ‘Mentor.Zen-Net’ an innovative mobile application or ‘app’ designed to connect entrepreneurs with experts from various fields for personalized mentorship. The primary aim of Mentor.Zen-Net is to champion mentorship as a catalyst for innovative entrepreneurship and a sustainable economy, specifically to advocate social sustainability for human capital. Through exchanging knowledge and professional guidance, the app seeks to empower aspiring entrepreneurs to realize their potential and drive forward-thinking business practices. The introduction emphasizes the transformative power of mentorship in the recent rapidly evolving economic landscape and the potential of the app to bridge the gap between emerging entrepreneurs and experienced mentors. The design and methods section elaborates on the target audience, core features, extensive market research, phased development plan, and strategic marketing approach. Key features of the app include a user-friendly interface, customized mentorship matching, and comprehensive resource libraries. The design of Mentor.Zen-Net focuses on creating an intuitive user experience, leveraging advanced technical architecture, and ensuring secure data management. Results and discussion anticipate high user engagement and satisfaction, leading to significant growth in innovative business ventures and sustainable practices. The conclusion reaffirms the app's mission to revolutionize access to mentorship, drive entrepreneurial innovation, and contribute to a sustainable economic future. Mentor.Zen-Net stands as a testament to the power of mentorship in fostering creativity, resilience, and sustainable growth within the entrepreneurial community. This business plan provides a clear and actionable framework for Mentor.Zen-Net's strategic business plan. Future direction will be on the development, implementation and commercialization of the app. Thus, ensuring its long-term impact and viability in the market. Through strategic business planning, Mentor.Zen-Net is poised to become an essential tool for aspiring entrepreneurs and mentors alike, championing the values of innovative entrepreneurship and sustainability.